Tanuláselméletek és összehasonlításaik: LEARNING THEORIES AND THEIR COMPARISON - Benke, Mariann (Közép-Európai Közlemények, 2020)
According to Buchanan and Huczinsky1 learning has an important role in a person’s life because we can achieve better salary with learning. Learning is also important for companies because it can influence the performance of individuals. Learning is a part of the work process therefore learning and work are each other’s consequences so we can’t separate this two subjects from each other. Learning is not only about collecting the right answers and information learning. It is thinking about our experiences. Organizational learning is a consciously planned effort to learn.2 “We can speak about learning when your behavior permanently change because of the result of your experience.”3 Buchanan-Huczinsky4 distinguish behaviorist and cognitive learning theories, Ertmer – Newby5 and Kispál-Vitai6 completes this with the constructivist learning theory. According to Schunk7 among cognitive theories there are learning theories which focuses on information processes. Virág8 completes the methodology with the view of connectivism which refers to the digitalization and development of learning technology and methodology. The aim of this paper is to describe the definition of learning process and to explain the behavioral, cognitive, and constructive learning theories.